2023
DOI: 10.2147/orr.s406176
|View full text |Cite
|
Sign up to set email alerts
|

Knee Pain After Retrograde Intramedullary Nailing with Surgical Implant Generation Network of Femur Shaft Fractures at Public Hospitals in Bahir Dar City, Ethiopia: Analysis of 6-Months Follow-Up Results

Abstract: Background The incidence of femur fractures in young and elderly people has increased, particularly in countries with limited resources like Ethiopia. Intra-medullary nailing (IM) has been an effective and cost-effective method of treating long bone shaft fractures, but it can lead to complications such as knee pain. Purpose This study aimed to evaluate knee pain and its associated factors following retrograde intramedullary nailing for femur fractures. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…In Ethiopia, Birlie et al [ 26 ] studied postoperative knee pain at six months in 110 patients treated with retrograde femoral nailing using the SSN® and SFN®. They reported that retrograde intramedullary nail fixation is an effective method for femoral midshaft fractures but may cause knee pain at six months in 36.4% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, Birlie et al [ 26 ] studied postoperative knee pain at six months in 110 patients treated with retrograde femoral nailing using the SSN® and SFN®. They reported that retrograde intramedullary nail fixation is an effective method for femoral midshaft fractures but may cause knee pain at six months in 36.4% of patients.…”
Section: Discussionmentioning
confidence: 99%